Increasing Student Literacy In Learning Indonesian Through The CTL Model For Class 4 SDN Telanng 2 - Desvia Nur Afrida; Emelya Qoffayana (Yayasan Pondok Pesantren Nurul Islam Mojokerto, 2024)
This study examines the interest and understanding of students' literacy in learning the Indonesian language in schools. The aim of improving students' literacy in learning the Indonesian language is to enhance students' interest and understanding of reading and writing literacy, especially in Indonesian language learning. The design of this paper uses qualitative research, and the method used in this research is descriptive method, which will examine and describe how reading and writing literacy can affect students in Indonesian language learning. The subjects in this study focus on students of grade IV and teachers as homeroom teachers of grade IV at SDN Telang 2. The results of this study indicate a lack of interest and understanding of students in literacy in Indonesian language learning. Teachers choose to use the Contextual Teaching and Learning (CTL) model in Indonesian language learning to improve students' understanding of literacy.